Tindak Tutur Lokusi pada Video Pembelajaran Pendidikan Kewarganegaraan dalam Kanal Youtube Kejarcita (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2026)
This study aims to describe and identify the forms of locutionary speech acts that appear in Civic Education learning videos on the Kejarcita YouTube channel. Kejarcita is a YouTube channel that provides learning educational content for both senior high school and junior high school students. The language style used in the videos is highly engaging, beginning with a friendly greeting and informal style, such as “teman kece”, followed by questions that serve as an interactive means encourage viewers to think. The results of this study serve as a reference for gaining knowledge and understanding of the use of locutionary speech acts in learning videos on the Kejarcita channel. They may also be used as a reference for other researches who wish to conduct similar studies in the field of pragmatics or digital learning media. This research employs a descriptive qualitative method with a pragmatic approach. The data consist of utterances containing locutionary acts, taken from Civic Education learning videos on the Kejarcita YouTube channel. Based on the results of the analysis, 191 data points were obtained, namely (1) locutionary speech acts intended to inform, totaling 63 occurrences; (2) locutionary speech acts intended to explain, totaling 49 occurrences; (3) locutionary speech acts intended to ask, totaling 34 occurrences; (4) locutionary speech acts intended to invite, totaling 27 occurrences; and (5) locutionary speech acts intended to remind, totaling 18 occurrences.